Self-healing behavior of epoxy-based double-layer nanocomposite coatings modified with Zirconia nanoparticles - Sehrish Habib (17302699) (2021)
This work reports the self-healing behavior of epoxy-based double-layer nanocomposite coatings designed to mitigate corrosion in various industrial applications. Zirconia (ZrO2) nanoparticles were used as a carrier to load separately self-healing agent, polyethyleneimine (PEI), and corrosion inhibitor, imidazole (IM). The loaded ZrO2 nanoparticles with IM and PEI were doped into the epoxy matrix and applied on polished steel substrate to form pre and top layers of nanocomposite coatings, respectively. TEM analysis confirms the almost globular morphology of the zirconia nanoparticles with a particle size of 15–25 nm. The chemical bonding interactions among various species were confirmed through FTIR. The synergistic effect of self-healing agent and corrosion inhibitor in epoxy-based double-layer nanocomposite coatings demonstrated the pH and time dependence release of inhibitor and self-healing agent. A comparative EIS analysis conducted in 3.5 wt% NaCl solution reveals that epoxy-based double-layer nanocomposite coatings demonstrate improved corrosion resistance performance as compared to the blank epoxy and single layer epoxy reinforced coatings. This enhanced corrosion resistance of epoxy-based double-layer nanocomposite coatings can be ascribed to the efficient release of loaded IM and PEI in response to the external stimuli and can be potentially considered to circumvent corrosion in oil & gas and marine applications. Other Information Published in: Materials & Design License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.matdes.2021.109839